Anxiety, depression, and end‐of‐life care utilization in adults with metastatic cancer. Issue 11 (10th July 2021) - Mossman, Brenna; Perry, Laura M.; Walsh, Leah E.; Gerhart, James; Malhotra, Sonia; Horswell, Ronald; Chu, San; Raines, Amanda M.; Lefante, John; Blais, Christopher M.; Miele, Lucio; Melancon, Brian; et al.
Abstract: Objective: End‐of‐life care for patients with cancer is often overly burdensome, and palliative and hospice care are underutilized. The objective of this study was to evaluate whether the mental health diagnoses of anxiety and depression were associated with variation in end‐of‐life care in metastatic cancer. Methods: This study used electronic health data from 1, 333 adults with metastatic cancer who received care at two academic health centers in Louisiana, USA, and died between 1/1/2011–12/31/2017. The study used descriptive statistics to characterize the sample and logistic regression to examine whether anxiety and depression diagnoses in the six months before death were associated with utilization outcomes (chemotherapy, intensive care unit [ICU] visits, emergency department visits, mechanical ventilation, inpatient hospitalization, palliative care encounters, and hospice utilization), while controlling for key demographic and health covariates. Results: Patients (56.1% male; 65.6% White, 31.1% Black) commonly experienced depression (23.9%) and anxiety (27.2%) disorders within six months of death. Anxiety was associated with an increased likelihood of chemotherapy (odds ratio [OR] = 1.42, p = 0.016), ICU visits (OR = 1.40, p = 0.013), and inpatient hospitalizations (OR = 1.85, p < 0.001) in the 30 days before death. Anxiety (OR = 1.95, p < 0.001) and depression (OR = 1.34, p = 0.038) were associated with a greater likelihood of a palliative encounter. Conclusions: Patients with metastatic cancer who had an anxiety disorder were more likely to have burdensome end‐of‐life care, including chemotherapy, ICU visits, and inpatient hospitalizations in the 30 days before death. Depression and anxiety both increased the odds of palliative encounters. These results emphasize the importance of mental health considerations in end‐of‐life care.